1998
DOI: 10.1292/jvms.60.1093
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Bottle-Nosed Dolphin (Tursiops truncatus) MHC Class I cDNA.

Abstract: ABSTRACT. Using polymerase chain reaction, bottle-nosed dolphin (Tursiops truncatus) major histocompatibility complex (DoLA) class Iα chain cDNA was cloned and sequenced. Predicted amino acid sequences of DoLA class Iα chain have cystein residues for intradomain disulfide bond formation and N-linked glycosylation sites, suggesting that DoLA class Iα chain molecules construct α1, α2, and α3 domain structures. Similarity of DoLA class Iα chain cDNA to land mammal MHC class Iα chain cDNA was 90.4% in cattle, 90.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Currently, studies on the genetic variation of MHC class I genes in cetaceans are limited, although some studies have been reported for the fin whale (Balaenoptera physalus), the sei whale (Balaenoptera borealis), the gray whale (Eschrichtius robustus), the finless porpoise (Neophocaena phocaenoides), and the North Atlantic right whale (Eubalaena glacialis) (Flores-Ramirez et al 2000, 2004Gillett et al 2014;Trowsdale et al 1989;Xu et al 2007). In addition, cDNA amplification has been used to confirm the expression of MHC class I genes in the bottlenose dolphin (Tursiops truncatus) and Hector's dolphin (Cephalorhynchus hectori) (Heimeier et al 2009;Shirai et al 1998). Most studies suggest the presence of at least three MHC class I loci in cetaceans.…”
mentioning
confidence: 99%
“…Currently, studies on the genetic variation of MHC class I genes in cetaceans are limited, although some studies have been reported for the fin whale (Balaenoptera physalus), the sei whale (Balaenoptera borealis), the gray whale (Eschrichtius robustus), the finless porpoise (Neophocaena phocaenoides), and the North Atlantic right whale (Eubalaena glacialis) (Flores-Ramirez et al 2000, 2004Gillett et al 2014;Trowsdale et al 1989;Xu et al 2007). In addition, cDNA amplification has been used to confirm the expression of MHC class I genes in the bottlenose dolphin (Tursiops truncatus) and Hector's dolphin (Cephalorhynchus hectori) (Heimeier et al 2009;Shirai et al 1998). Most studies suggest the presence of at least three MHC class I loci in cetaceans.…”
mentioning
confidence: 99%
“…Since a whaling moratorium in 1945, the population appears to have recovered from an estimated 3000 to approximately 20,000 individuals ( Buckland et al 1993;Henderson 1984). Aspects of gray whale behavior and (Shirai et al 1998) MHC-I (a) exon 2 and (b) exon 3 sequences with mouse ( H2-K b , U47328), ( H2-K d , U47329); leopard ( LPAI69J, U07676); cheetah (AJUI1, U07665); harbor seal (PLA-A1, U88874); human ( HLA-B-0701, U21052); cattle ( BoLA, AB008626); and swine (SLA-I, AF074426). Sequences were aligned using the Clustal-W program ( Thompson et al 1994).…”
mentioning
confidence: 99%
“…5). The bottlenose dolphin sequence shown in the alignment (see Supporting Figure S4) has not been deposited in GenBank and was entered directly from the published article (Shirai et al . 1998).…”
Section: Resultsmentioning
confidence: 99%
“…2000, 2004), the finless porpoise ( Neophocaena phocaenoides ) (Xu et al . 2007), the vaquita ( Phocoena sinus ) (Munguia‐Vega 2003), and in the bottlenose dolphin ( Tursiops truncates ) (Shirai et al . 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation